(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The results of in vitro propagation of the plants from the collection of the Botanical Garden named after F.N. Rusanov of the ASc RUz – Corylus avellana L. (Betulaceae Gray). The protocol of sterilization, the concentration and content of nutrient medium allowing propagation of the hazelnut in in vitro conditions are given in this article.